Influence of the column rectangularity index and of the boundary conditions in the punching resistance of slab-column connections - PAIVA,O. S. (2015)
Experimental evidence indicates that both the column rectangularity index and the boundary conditions of the connection may affect the ultimate punching resistance. This paper presents general aspects of these topics and, through the analysis of experimental results of tests on 131 slabs, evaluates the accuracy and suitability of recommendations presented by ABNT NBR 6118, Eurocode 2, ACI 318 and fib Model Code 2010. Experimental results showed that the security level of normative estimates trend to reduce as the column rectangularity increases, and in some cases, the punching resistance was overestimated. Finally, adjustments are suggested in equations presented by NBR 6118 and MC2010 in order to eliminate this trend of unsafe results.